Improving economic position of Vietnam in Asean Economic Community (AEC) from the global integration perspectives - Hong, To Thi Kim; Tuan, Nguyen Anh; Dao, Tran Thi Kim; Duc, Nguyen Minh (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
After participating in ASEAN, and through various dialogue mechanisms, Vietnam now has become a more important and comprehensive economic member of the ASEAN Economic Community. This study focuses on analyzing the process of participating in the ASEAN Community and the roles and contributions of Vietnam in this organization to affirms Vietnam's position in the process of forming the AEC and demonstrates Vietnam's priorities for the integration process. The paper uses the primary and secondary data by using tools of desk research of different data in relativeness and by the quantitative method by using the Cobb-Doughlas function with a logarithmic form. The paper confirms the integration of Vietnam's economy into the ASEAN Economic Community (AEC) is an inevitable development after the achieved results of ASEAN's cooperation and economic connection. The AEC is an open regional economic integration model. The implementation of the AEC will bring in multi-dimensional impacts on member countries, and the extent of these impacts will depend on the level of regional and international economic integration, competitiveness, and effectiveness of policy reform in each country.